Surgical treatment of severe aortic stenosis using a sutureless biological valve - Kaitović Marko; Mićović Slobodan (Medicinski Podmladak)
Severe aortic stenosis (AS) is the most common degenerative valvular heart disease. Given the global aging of the population, it is estimated that the prevalence of severe AS will increase by 300% by year 2050. Surgical replacement of the stenotic aortic valve is still the standard treatment protocol for patients with low and intermediate operative risk. In routine practice of surgical treatment of severe AS in people older than 65 years, biological valves (biovalves) have gradually replaced the mechanical valves. Biovalves can be stented (sutured) or sutureless. Sutured valves are implanted to the aortic annulus using a surgical thread, while sutureless valves are implanted using a pressurized balloon. Previous studies have shown that the advantages of the easier technique of implantation of sutureless valve over the stented valves are the shortening of the operative period, i.e. reduction in time of cardiac arrest and extracorporeal circulation and minimally invasive surgical approach. It must be pointed out that the price of new sutureless valves is on average 10 times more expensive than the price of the stented biovalves. Therefore, the use of these valves in healthcare systems with limited resources can be considered only in patients in whom they would prevent many potential complications during and after the aortic valve replacement. For example, the implantation of a sutureless valve allows less manipulation of the aorta, which is especially important in patients whose aortic root is calcified and worn off, and to prevent the operioperative stroke. Also, patients with a small aortic annulus have a greater benefit from the implantation of a sutureless valve due to the larger effective orifice area, which gives way to better hemodynamic characteristics. Considering that sutureless valves have only been implanted for the past ten years in Europe, numerous studies are limited to the assessment of early and midterm outcomes (on average 5 years of follow-up), such as survival, structural valvular deterioration rate, infective endocarditis rate and reoperation rate. Therefore, prospective cohort studies evaluating long-term outcomes after sutureless valve implantation are warranted.